Pengaruh Latihan Squat Terhadap Peningkatan Power Tungkai Siswa Ekstrakulikler Bolavoli di SMP Negeri 1 Karanggeneng Lamongan - Mochammad Ainun Najih; Fatkur Rohman Kafrawi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of squat training on increasing the leg power of volleyball extracurricular students at SMP Negeri 1 Karanggeneng Lamongan. Leg power is an important factor in volleyball athletes' performance, especially in making jumps for smashes and blocks. Squat exercises were chosen because they are effective in increasing the strength of the leg muscles, which contributes to increased jumping explosiveness.The research method used was an experiment with a pretest-posttest design in two groups: the group that was given barbell squat exercises and the control group without treatment. The research sample consisted of 24 students who were members of volleyball extracurriculars. Limb power measurements were carried out using vertical jump tests before and after treatment. Data analysis uses normality test, homogeneity test, and t-test with the help of SPSS software. The results showed that there was a significant increase in limb power in both treatment groups compared to the control group. The squat barbell group showed a higher increase compared to the control group without treatment. This shows that squat exercises, especially with additional weight, have a positive effect on increasing leg power. Based on these findings, it is recommended that squat exercises be included in students' physical training programs, especially in volleyball, to improve athletes' jumping performance. In addition, further research with longer exercise durations and larger sample sizes is recommended to obtain more comprehensive results.